Pengaruh Penggunaan Alat Peraga Roda Trigonometri Terhadap Hasil Belajar Matematika - Sinaran, Herlina Sinaran; Sahidi, Sahidi; Pamungkas, Dwi (THEOREMA: The Journal Education of Mathematics, 2023)
The purpose of this study is to ascertain how visual aids affect thelearning results for mathematics in class X Multimedia 2 at SMK YPKImanuel, Sorong City. There were fifteen students that participated in thisstudy. methods of gathering data through surveys, tests, and documentation.The normalcy and hypothesis tests are the data analysis techniques that areemployed. Shapiro-Wilk is the normality test that was employed, and apaired sample t-test was utilized for the hypothesis test. The data is normallydistributed since, according to the Shapiro-Wilk test results, the pretestsignificance value is 0,378 > 0,05 and the posttest 0,251 > 0,05. Accordingto the study's findings, students in class X Multimedia 2 had learningoutcomes before the treatment (pretest) of 37.87% and after the treatment(posttest) of 77.33%. This means that there was a 39.46% difference betweenthe pretest and posttest scores, indicating that the use of this teaching aid hada positive effect on students' learning. These findings indicate that the usageof the trigonometry wheel teaching aid has an impact on the learningoutcomes for mathematics in class X Multimedia 2 at SMK YPK Imanuel,Sorong City.Keywords : Teaching Aids, Trigonometry, learn math.